2003
DOI: 10.1016/s0006-2952(03)00153-9
|View full text |Cite
|
Sign up to set email alerts
|

N6-Substituted adenosine derivatives: selectivity, efficacy, and species differences at A3 adenosine receptors

Abstract: The activation of the human A(3) adenosine receptor (AR) by a wide range of N(6)-substituted adenosine derivatives was studied in intact CHO cells stably expressing this receptor. Selectivity of binding at rat and human ARs was also determined. Among N(6)-alkyl substitutions, small N(6)-alkyl groups were associated with selectivity for human A(3)ARs vs. rat A(3)ARs, and multiple points of branching were associated with decreased hA(3)AR efficacy. N(6)-Cycloalkyl-substituted adenosines were full ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
206
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(221 citation statements)
references
References 25 publications
12
206
0
2
Order By: Relevance
“…Similar to previous studies of the N 6 -position [8] and the ribose moiety [9,30,31], structural determinants at the 2-position of adenosine have been found to be critical for A 3 AR recognition and activation. Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to previous studies of the N 6 -position [8] and the ribose moiety [9,30,31], structural determinants at the 2-position of adenosine have been found to be critical for A 3 AR recognition and activation. Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Radioactivity was determined in a Beckman 5500B γ-counter. The binding of [ 3 H]R-PIA to A 1 receptors and the binding of [ 3 H]CGS21680 to A 2A receptors were as previously described [8].…”
Section: Binding Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In an effort to develop potent agonists and antagonists for A 3 ARs, a wide range of N 6 -and 2′-substituted adenosine derivatives have recently been pharmacologically characterized [8][9][10]. We found that various adenosine derivatives, which were previously demonstrated to be agonists at A 1 and A 2A ARs and assumed to be full/partial agonists at A 3 ARs, are indeed antagonists at this subtype.…”
Section: Introductionmentioning
confidence: 78%